2012
DOI: 10.1097/jto.0b013e318262de4a
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of Erlotinib and Hydroxychloroquine in Advanced Non–Small-Cell Lung Cancer

Abstract: Introduction This investigator-initiated study explores the safety, maximum tolerated dose (MTD), clinical response, and pharmacokinetics (PK) of hydroxychloroquine (HCQ) with and without erlotinib in patients with advanced non-small cell lung cancer (NSCLC). Methods Patients with prior clinical benefit from an epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor were randomized to HCQ or HCQ plus erlotinib in a 3+3 dose escalation schema. Results Twenty-seven patients were treated, 8 with HCQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(102 citation statements)
references
References 28 publications
3
99
0
Order By: Relevance
“…By far, numbers of basic studies and clinical trials evaluating such effect in cancer treatment are in progress [11,19,20,21,22,23,24,25,26]. However, the published results were in conflict.…”
Section: Introductionmentioning
confidence: 57%
“…By far, numbers of basic studies and clinical trials evaluating such effect in cancer treatment are in progress [11,19,20,21,22,23,24,25,26]. However, the published results were in conflict.…”
Section: Introductionmentioning
confidence: 57%
“…2,15 The most well-known example is selection of patients eligible for EGFR inhibition in metastatic lung cancer based on KRAS and EGFR mutational status. 3,5,[16][17][18][19] In this article, we compared the performance of five technical platforms for detecting mutations in FFPE-derived tumor DNA. All platforms, except the NGS-454, detected the (clinically relevant) mutations originally detected by the reference method.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in non-small cell lung tumor with the expression of wild-type EGFR, the combined use of chloroquine and erlotinib could overcome the resistance to erlotinib, and the use of gefitinib in combination can also increase the toxicity of gefitinib. The clinical phase I experiment of the combined use of chloroquine and erlotinib showed that the combined use of the two has good tolerance [39-41]. Therefore, the combination of CH12 and an autophagy inhibitor to treat EGFRvIII-positive hepatocellular carcinoma is worth further exploration.…”
Section: Discussionmentioning
confidence: 99%